Helminth and respiratory mite lesions in Pinnipeds from Punta San Juan, Peru - Calderón Mayo, Karla Ines (2018)
The tissues and parasites collected from Peruvian fur seals (Arctocephalus australis) and South American sea lions (Otaria byronia) found dead at Punta San Juan, Peru were examined. The respiratory mite, Orthohalarachne attenuata infected 3 out of 32 examined fur seals and 3 out of 8 examined sea lions, however caused moderate to severe lymphohistiocytic pharyngitis only in fur seals. Hookworms, Uncinaria sp, infected 6 of the 32 examined fur seals causing variable degrees of hemorrhagic and eosinophilic enteritis. This parasite caused the death of 2 of these pups. In fur seals and sea lions, Corynosoma australe and Contracaecum osculatum were not associated with significant tissue alterations in the intestine and stomach respectively. Respiratory mites and hookworms have the potential to cause disease and mortality among fur seals, while parasitic infections do not impact significatively the health of sea lions at Punta San Juan, Peru.